HUBUNGAN ANTARA KECERDASAN EMOSIONAL DAN COPING STRATEGY PADA TARUNA TINGKAT I DAN II SEKOLAH TINGGI PERIKANAN BOGOR - NURUL MAULIDYA SEKAR FARDHANI; Ika Febrian Kristiana (Faculty of Psychology, Diponegoro University, 2017)
Official school requires students or cadets to have a tough both mentally and physically. The boarding campus life with the social and academic demands faced by cadets often become a stressors during their college life. The effort that individuals do in dealing with stressor is called coping strategy. The aim of this study is to determine the relationship between emotional intelligence with coping strategy at Bogor Fisheries College Cadets (STP Bogor). Emotional intelligence is the ability of the individual to recognize the emotions of oneself and the emotions of others and use their emotions to overcome the demands in the environment. The subjects of this study are 134 cadets obtained with cluster random sampling technique. The measuring instruments used in this study are coping strategy scale (65 items, α = .950), and emotional intelligence scale (31 items, α = .914). The data analysis method used in this research is simple regression analysis. The result showed that there was a significant positive correlation between emotional intelligence and coping strategy of cadets with correlation coefficient (r = 0.676; p = .000; p <.05). Emotional intelligence contributes effectively to 45.7% in coping strategy.